Literatura Brasileira: Autoritarismo, Violência, Melancolia / Brazilian literature: authoritarianism, violence, melancholy - Ginzburg, Jaime (Revista de Letras, 2007)
Relacionando historia e literatura, este artigo procura avaliar efeitos traumáticos da violência e do autoritarismo na literatura brasileira, considerando a presença de melancolia nas obras examinadas. O ensaio toma o pensamento de Theodor Adorno como base teórica e discute livros recentes ligados ao assunto, escritos por Moacyr Scliar, Idelber Avelar e Fernando Anrenas.Connecting History and Literature, this study tries to examine some aspects of the traumatic effects of violence and authoritarianism is Brazilian Literature. It also considers the strong presence of melancholy in literary words. The essay respects Theodor Adorno’s thought, as a theoretical basis. Recent books written by Moacyr Scliar, Idelber Avelar and Fernando Arenas, related to the subject, are discussed.